Different Treatments of Symptomatic Angiomyolipomas of the Kidney: Two Case Reports (Journal of Kidney Cancer, 2021)
Development of more sensitive imaging techniques has caused an increase in the number of diagnosed small renal tumors. Approximately 2–3% of these lesions are proved to be angiomyolipomas (AML), a rare benign tumor of the kidney sometimes causing pain and hematuria. The most required approach is observation, but in the case of recurrent symptoms or larger tumors, which may cause bleeding, a more active treatment is required. We present two cases of symptomatic AML tumors of different sizes in the kidney: one treated with transarterial embolization (TAE), and the other with percutaneous cryoablation (CRA). The lesions were diagnosed on the basis of contrast-enhanced computed tomography (CT) scan and magnetic resonance imaging (MRI). Both treatments proved to be effective and safe for treating renal AMLs. A follow-up carried out, based on contrast-enhanced CT scan, confirmed complete treatment of AML and decreased lesion size. There are myriad minimally invasive approaches for the treatment of renal AMLs, and the preservation of renal function remains a priority. The most popular treatment option is the selective renal artery embolization. Owing to its limited invasiveness, CRA could be an attractive option for the preventive treatment of AML.